INOVASI ECO-CRAFT BERBASIS LIMBAH KULIT KERANG LAUT UNTUK PEMBERDAYAAN UMKM AYU & BAGUS COLLECTION DI DESA SERANGAN - Nutrisia Dewi, Ni Made Emmi; Wika Artawan, I Kadek; Agung Kepakisan Mandala, I Gusti Ngurah; Pradnya Paramita, Ni Kadek Ayu; Asteria Putri, Putu Yudha; Emilika Budi Lestari, Ni Putu; Pranajaya, I Kadek; Prasiani, Ni Komang; Yogantari, Made Vairagya; Dwi Mahadipta, Ngurah Gede; Sintia Dewi, Ni Kadek Tarisa (Universitas Kadiri, 2025)
Serangan Village, as a coastal area, generates a large amount of shell waste that has the potential to be processed into products with economic value. This community service program aims to enhance the capacity of Ayu & Bagus Collection MSMEs in Serangan Village through eco-craft innovations based on marine shell waste. The implementation methods include needs assessment, training, mentoring, and the provision of supporting facilities. The training covers product design based on local wisdom, business management, digital marketing strategies, and the use of technology in production and promotion. In addition, the community service team provided various supporting tools, such as production and finishing equipment, funded by a grant from the Directorate of Research, Technology, and Community Service, Directorate General of Research and Development, Ministry of Higher Education, Science, and Technology, in the 2025 Fiscal Year. The results indicate an increase in product quantity, improved skills of partners in producing more creative eco-craft designs, more structured business management, and better utilization of digital media for marketing. The provision of equipment also supports business sustainability by accelerating production and improving product quality. This program contributes directly to the empowerment of MSMEs and environmental preservation through the utilization of shell waste. Thus, the collaboration of training and facility provision demonstrates a potential model of community empowerment through eco-craft that is competitive, sustainable, and rooted in local potential.